Effect of Study Design and Survey Instrument to Identify the Association Between Depressive Symptoms and Physical Activity in Type 2 Diabetes, 2000-2018: A Systematic Review. Issue 1 (February 2020) - Lee, Jusung; Callaghan, Timothy; Ory, Marcia; Zhao, Hongwei; Foster, Margaret; Bolin, Jane N.
Introduction: Previous studies have used a variety of survey measurement options for evaluating the association between physical activity (PA) and depressive symptoms, raising questions about the types of instruments and their effect on the association. This study aimed to identify measures of PA and depressive symptoms and findings of their association given diverse instruments and study characteristics in type 2 diabetes (T2DM). Methods: Online databases, Medline, Embase, CINAHL, and PsycINFO were searched on July 20, 2018, and January 8, 2019. Our systematic review included observational studies from 2000 to 2018 that investigated the association between PA and depressive symptoms in T2DM. Results: Of 2294 retrieved articles, 28 studies were retained in a focused examination and comparison of the instruments used. There were a range of standard measures, 10 for depressive symptoms and 7 for PA, respectively. Patient Health Questionnaire (PHQ) for depressive symptoms and study-specific methods for PA were the most popular. Overall, 71.9% found a significant association between PA and depressive symptoms. Among studies classified as high quality or reliability, the figure was 81.8%. Conclusion: A majority of the sample found an association between depressive symptoms and PA, which is fairly consistent across study characteristics. The findings provide the evidence for the health benefits of PA on reducing depressive symptoms in persons with T2DM, suggesting active engagement in PA for effective diabetes management. However, guidelines for objective measurements and well-designed prospective studies are needed to strengthen the evidence base and rigor for the association and its directionality.